2010
DOI: 10.1002/dvdy.22376
|View full text |Cite
|
Sign up to set email alerts
|

The TGFβ type II receptor plays a critical role in the endothelial cells during cardiac development

Abstract: TGFb signalling is required for normal cardiac development. To investigate which cell types are involved, we used mice carrying a floxed Type II TGFb receptor (Tgfbr2fl) allele and Cre-lox genetics to deplete this receptor in different regions of the heart. The three target tissues and corresponding Cre transgenic lines were atrioventricular myocardium (using cGata6-Cre), ventricular myocardium (using Mlc2v-Cre), and vascular endothelium (using tamoxifen-activated Cdh5(PAC)-CreERT2). Spatio-temporal Cre activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…Similarly, the majority of mice that had myocardial specific depletion of Tgfbr2 also developed normal hearts. This finding was observed in two independent studies using two different Cre lines, Mlc2v-Cre and cTnT-Cre, (Jiao et al, 2006;Robson et al, 2010) confirming that TGFb signaling has little role in cardiomyocyte cells during heart development.…”
Section: Larsson Et Al 2001supporting
confidence: 77%
See 1 more Smart Citation
“…Similarly, the majority of mice that had myocardial specific depletion of Tgfbr2 also developed normal hearts. This finding was observed in two independent studies using two different Cre lines, Mlc2v-Cre and cTnT-Cre, (Jiao et al, 2006;Robson et al, 2010) confirming that TGFb signaling has little role in cardiomyocyte cells during heart development.…”
Section: Larsson Et Al 2001supporting
confidence: 77%
“…(2) embryonic lethal at ED15.5 when Cre activated at ED 11.5, VSD, cerebral hemorrhage VSD Carvalho et al, 2007;Jiao et al, 2006;Robson et al, 2010 Tgfbr2/vascular smooth muscle/epicardium (1) Embryonic lethal at approximately ED 17, VSD, aortic dilatation, coronary vessel defects;…”
Section: Larsson Et Al 2001mentioning
confidence: 99%
“…As the αVβ8 integrin has been shown to mediate TGFβ activation in vitro (Cambier et al, 2005), this suggested that αVβ8 on neuroepithelial cells activates TGFβ, which subsequently promotes vascular integrity. The similarities in phenotype of neuroepithelialspecific Itgav and Itgb8 mutants with endothelial-specific mutations of Tgfbr2 (Robson et al, 2010), Alk5 (Nguyen et al, 2011) and Smad2/Smad3 (Itoh et al, 2012) support this proposal. In each mutant, vessels were 'stalled' in their growth from the pia mater towards the ventricle.…”
Section: Introductionmentioning
confidence: 68%
“…Glomeruloid formation and hemorrhage are relatively late phenotypes, probably secondary to elevated sprouting, branching and proliferation of endothelial cells. In addition to Itgav and Itgb8, brain hemorrhage during embryonic development is observed in other mutant mice, including Gpr124 (Anderson et al, 2011;Cullen et al, 2011;Kuhnert et al, 2010), Nrp1 (Gerhardt et al, 2004;Gu et al, 2003;Kawasaki et al, 1999), Wnt7a/ b-Bcat (Daneman et al, 2009;Liebner et al, 2008;Stenman et al, 2008), Tgfb1/3 (Mu et al, 2008), Tgfbr2 (Nguyen et al, 2011;Robson et al, 2010), Alk5 (Nguyen et al, 2011), Smad4 , Smad2/Smad3 (Itoh et al, 2012) and S1pr1 (Gaengel et al, 2012). Prior work either did not address the cause of hemorrhage (Nrp1, Tgfb1/3, Smad2/Smad3, S1pr1) or attributed it to a dysfunctional BBB [Gpr124 (Anderson et al, 2011), Bcat (Liebner et al, 2008), Smad4 , Itgb8 (Mobley et al, 2009), Itgav-Tgfbr2-Alk5 (Nguyen et al, 2011)].…”
Section: Discussionmentioning
confidence: 99%
“…This data suggests that TβRII is not involved in initial cushion formation and EMT but rather proliferation of cushion mesenchyme. If deletion of TβRII is induced using tamoxifen at E11.5 using a CreERT system (tamoxifen-activated Cdh5(PAC)-CreERT2) in the endothelium, embryos die at E15.5 due to abnormal ventricular septation, failure of cushion fusion and haemorrhaging in cerebral blood vessels [96].…”
Section: Tgfβ Signalling In Cardiac Valve Developmentmentioning
confidence: 99%